2021
DOI: 10.1017/s0263574721001582
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual design and error analysis of a cable-driven parallel robot

Abstract: This paper develops the conceptual design and error analysis of a cable-driven parallel robot (CDPR). The earlier error analysis of CDPRs generally regarded the cable around the pulley as a center point and neglected the radius of the pulleys. In this paper, the conceptual design of a CDPR with pulleys on its base platform is performed, and an error mapping model considering the influence of radius of the pulleys for the CDPR is established through kinematics analysis and a full matrix complete differential me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…This method takes all the above errors as unknown quantities, the LS method is used to solve the optimal error parameters, and compensates directly in the target measurement results finally. For this purpose, Equation (11) needs to be turned into a display expression. Since the error components values are relatively small, they can be considered in mathematical operation as follows:…”
Section: Ls-based Error Compensation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method takes all the above errors as unknown quantities, the LS method is used to solve the optimal error parameters, and compensates directly in the target measurement results finally. For this purpose, Equation (11) needs to be turned into a display expression. Since the error components values are relatively small, they can be considered in mathematical operation as follows:…”
Section: Ls-based Error Compensation Methodsmentioning
confidence: 99%
“…Furthermore, for the robot, Feng used a homogeneous transformation matrix to develop the mapping relationship between the end-effector position error and geometric source errors within the serial mechanism kinematic chains, and studied the kinematics of the spatial serial mechanism with a large number of geometric errors [ 10 ]. Li used a full matrix complete differential method to construct the error model of a cable-driven parallel robot, the results confirmed that the cable length errors and pulleys’ geometric errors should be given higher priority in design [ 11 ]. San built the error mapping model for the parallel mechanism part of the hybrid robot by using the closed-loop vector method and the first-order perturbation method, and identified the most significant factors affecting the robot’s end posture error, but no error compensation [ 12 ].…”
Section: Introductionmentioning
confidence: 97%
“…), but their use on a miniaturised scale and in under-sensitive systems is very limited [5,19]. Recently, redundant cable-driven parallel robots (CDPRs) have been used not only for actuation but also for force distribution sensitivity [5,[19][20][21][22][23][24][25], applied in many domains such as rehabilitation [26], and defining cable tension sensitivity analysis for macroscopic applications, such as maintaining a camera in suspension for a football match [27]. Cable-driven systems are also used to achieve maximum workspace and isotropic force exertion, such as shown in [28].…”
Section: Introductionmentioning
confidence: 99%